2021
DOI: 10.47672/ejps.748
|View full text |Cite
|
Sign up to set email alerts
|

Levels of Hydroquinone, Selected Heavy Metals (Hg, Pb, As) and Chemical requirements in Some Skin Lightening Creams Sold in Mbarara Municipality

Abstract: In this study, Skin-lightening creams commonly sold in Mbarara municipality were analyzed for chemical parameters (pH, thermal stability and fatty substance content), total hydroquinone, Lead, Mercury, and Arsenic contents. Total heavy metal content was determined by atomic absorption spectrophotometry. The levels of hydroquinone were determined using High Performance liquid chromatography (HPLC). All the creams showed detectable mean levels of mercury, ranging from 0.07±0.01ppm to 0.33±0.01ppm. Only 26.31% of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 31 publications
2
4
0
Order By: Relevance
“…The pH of all the samples are acidic, it follows this trend; Sample 3 > Sample 1 > Sample 4 > Sample 2 (Table 2) andall falls below the permissible standard set by WHO except sample 3, the organic locally produced cream. The pH of human skin is acidic and ranges from4.5 to 6.So, application of acidic cream on skin may cause irritation and this can expose the skin to dermal diseases [28]. The pH recorded for creams in this study falls within the range reported by [29,30] Ekpunobi et al, [29], and Oyedeji et al, [30] but, higher than the results of Muloogi et al, [28].and Saleh et al, [31].…”
Section: Phsupporting
confidence: 68%
See 3 more Smart Citations
“…The pH of all the samples are acidic, it follows this trend; Sample 3 > Sample 1 > Sample 4 > Sample 2 (Table 2) andall falls below the permissible standard set by WHO except sample 3, the organic locally produced cream. The pH of human skin is acidic and ranges from4.5 to 6.So, application of acidic cream on skin may cause irritation and this can expose the skin to dermal diseases [28]. The pH recorded for creams in this study falls within the range reported by [29,30] Ekpunobi et al, [29], and Oyedeji et al, [30] but, higher than the results of Muloogi et al, [28].and Saleh et al, [31].…”
Section: Phsupporting
confidence: 68%
“…The pH of human skin is acidic and ranges from4.5 to 6.So, application of acidic cream on skin may cause irritation and this can expose the skin to dermal diseases [28]. The pH recorded for creams in this study falls within the range reported by [29,30] Ekpunobi et al, [29], and Oyedeji et al, [30] but, higher than the results of Muloogi et al, [28].and Saleh et al, [31].…”
Section: Phsupporting
confidence: 68%
See 2 more Smart Citations
“…HQ will darken when exposed to light and air because of its nature as a reducing agent. The hydroquinone level in the cream is only allowed to be 2%, if the hydroquinone level is > 2% then it is included in the group of hard drugs that can be used based on a doctor's prescription [8]. Therefore, the use of HQ with high levels in cosmetics has been prohibited [9].…”
Section: Introductionmentioning
confidence: 99%